Administration of All-Trans Retinoic Acid to Pregnant Sows Improves the Developmental Defects of Hoxa1−/− Fetal Pigs - Zhou, Haimei; Chen, Yixin; Hu, Yongqiang; Gao, Shan; Lu, Wei; He, Yuyong (Frontiers in Veterinary Science, 2021)
Hoxa1 mutation adversely affect fetal pig development, but whether all-trans retinoic acid (ATRA) administration to Hoxa1+/− pregnant sows can improve Hoxa1−/− fetal pig development defects has not been reported. A total of 24 healthy Hoxa1+/− sows were mated with a healthy Hoxa1+/− boar and randomly assigned to one control group and nine experiment groups. ATRA was orally administered to pregnant sows at the doses of 0, 4, 5, or 6 mg/kg maternal body weight on 12, 13, and 14 days post coitum (dpc), respectively, and a total of 146 live piglets were delivered including 37 Hoxa1−/− piglets and 109 non-Hoxa1−/− piglets. Results indicated that Hoxa1−/− piglets delivered by sows in control group had bilateral microtia, canal atresia and ear's internal defects, and had lower birth liveweight and external ear score than non-Hoxa1−/− neonatal piglets (P < 0.05). Maternal administration with ATRA can effectively correct the development defects of Hoxa1−/− fetal pigs, Hoxa1−/− neonatal piglets delivered by sows administered ATRA at a dose of 4 mg/kg body weight on 14 dpc had higher birth liveweight (P > 0.05) and higher scores of external ear (P < 0.05) compared to Hoxa1−/− neonatal piglets from the control group, but had no significantly difference in terms of birth liveweight and external ear integrity than non-Hoxa1−/− piglets from the control group (P > 0.05). The time of ATRA administration significantly affected Hoxa1−/− fetal development (P < 0.05). Administration of ATRA to Hoxa1+/− pregnant sows at 4 mg/kg body weight on 14 dpc can effectively improve the birth liveweight and ear defects of Hoxa1−/− piglets.